Upper limb kinematic differences between breathing and non-breathing conditions in front crawl sprint swimming - McCabe, C. B.; Sanders, R. H.; Psycharakis, S. G. (Journal of Biomechanics, 2015)
The purpose of this study was to determine whether the breathing action in front crawl (FC) sprint swimming affects the ipsilateral upper limb kinematics relative to a non-breathing stroke cycle (SC). Ten male competitive swimmers performed two 25 m FC sprints: one breathing to their preferred side (Br) and one not breathing (NBr). Both swim trials were performed through a 6.75 m3 calibrated space and recorded by six gen-locked JVC KY32 CCD cameras. A paired t-test was used to assess statistical differences between the trials, with a confidence level of p<0.05 accepted as significant. Swimmers were slower (3%) when breathing. Within the entry phase, swimmers had a slower COM horizontal velocity (3.3%), less shoulder flexion (8%), abduction (33%) and roll (4%) when breathing. The pull phase was longer in duration (14%) swimmers had a shallower hand path (11%), less shoulder abduction (11%), a slower hand vertical acceleration (30%) and slower centre of mass (COM) horizontal velocity (3%) when breathing. In the push phase, swimmers had a smaller elbow range of motion (ROM) (38%), faster backwards hand speed (25%) and faster hand vertical acceleration (33%) when breathing. Swimmers rolled their shoulders more (12%) in the recovery phase when breathing. This study confirms that swim performance is compromised by the inclusion of taking a breath in sprint FC swimming. It was proposed that swimmers aim to orient their ipsilateral shoulder into a stronger position by stretching and rolling the shoulders more in the entry phase whilst preparing to take a breath. Swimmers should focus on lengthening the push phase by extending the elbow more and not accelerating the hand too quickly upwards when preparing to inhale.